Harnessing ICT Use in Poverty Reduction: A Case Study of Rural Women in Keiyo South Constituency - Jebet, Lelon Lydia; Odero, Damaris; Agalo, Joyce (African Journal of Education, Science and Technology, 2018)
Information and communications technologies (ICTs) are powerful tools that boost economic growth and improve social development. However, despite an increase in ICT use, the socio-economic status of rural women in Kenya is still low. The purpose of this study, therefore, was to establish how ICT can be used to improve the social status of rural women in Keiyo South constituency, Elgeyo/Marakwet County, Kenya and recommend the best practices for improving the social well-being of rural women in Kenya. The primary objectives were; to establish the social benefits of ICT use among rural women in Keiyo South Constituency and find out the influence of ICT use on the social welfare of rural women. The study was informed by Harris Info-Mobilization theory. Using a descriptive survey research design, 141 respondents were drawn from a target population of 3070 women in Keiyo South by first stratifying the constituency into divisions and locations and then using purposive and snowball sampling techniques to obtain the actual respondents. Data was collected using semi-structured interview schedules supplemented by document review and observation and analyzed using descriptive statistics. The study found that the rural women of Keiyo South have limited access to ICT Technology and infrastructure which has impacted negatively on their socio-economic and political status. Access to information was principally through informal sources such as friends and neighbors; they lacked education and training to provide them with knowledge and skills for accessing ICT information which can help them improve their social status. The study concluded that use of ICT has contributed to improving the social status of rural women through economic empowerment and has enabled the rural women to obtain new life skills. Also, ICT has allowed them to participate in political election online. With appropriate ICT infrastructure and policies in place, ICT should be used to improve the socio-economic and political status of rural women in Keiyo South. In a bid to enhancing women participation in development, the study recommends that the county government enact policies and projects that support the development of ICT infrastructure and media information literacy competencies of the women. These would empower the women to develop better strategies for poverty reduction.
Keywords: ICT; Poverty Reduction; Rural women; Keiyo South Constituency